Implementasi Kepemimpinan Kepala Sekolah dalam Meningkatkan Mutu Pembelajaran di Sekolah Dasar (Studi Kasus Siswa SDN Cikandang Tanjungsari dan SDN Citali Pamulihan Kabupaten Sumedang) - Suharyanto H. Soro; Nurisah Sumartina; Abdul Azis; Muhamad Yusuf (LP. Ma'arif Janggan Magetan, 2024)
The school principal plays a crucial role in leading educational units to achieve their vision and mission, as mandated by Indonesian law. However, challenges persist, particularly in improving learning quality to produce academically accountable graduates. This study examines the leadership of school principals in enhancing learning quality at SDN Cikandang and SDN Citali, Sumedang. Using qualitative methods with a case study approach, data were collected through observation, interviews, and documentation. Findings reveal that principals significantly impact learning quality by adopting effective leadership strategies, including: (1) having a clear vision and effectively communicating it; (2) fostering open communication and active listening; (3) making decisive and accountable decisions; (4) demonstrating empathy towards team members; (5) upholding integrity to build trust; (6) adapting to challenges without losing focus; (7) nurturing team potential and motivating optimal performance; (8) resolving conflicts constructively; and (9) maintaining a lifelong learning mindset to enhance team capabilities. The success of a principal’s leadership depends on these qualities, combined with the context in which they lead. Such leadership not only addresses existing challenges but also drives schools toward achieving high-quality education.